Vacuum Assisted Vaginal Delivery in Singleton Term Pregnancies: Short Term Maternal and Neonatal Outcome in a Tertiary Hospital of Nepal - Shrestha, Buddhi Kumar; Shrestha, Subha; Thapa, Babita (Journal of Lumbini Medical College, 2017)
Introduction: Other than cesarean delivery, assisted vaginal delivery is an alternative procedure for delivery in emergency obstetrics. Presently, vacuum delivery has gained more popularity than forceps for operative/assisted vaginal delivery, when and where indicated, with success as well as lesser neonatal and maternal complications. This study was done to estimate the short term maternal and fetal morbidity/mortality due to vacuum assisted vaginal delivery.Methods: A prospective observational study was conducted at Lumbini Medical College Teaching Hospital from January 2015 to May 2016. One hundred and four pregnant women who had successful vacuum assisted vaginal deliveries were enrolled. Fetal and maternal outcome were assessed. Results: One hundred and four (2.9%) successful vacuum deliveries were conducted among 3457 deliveries during our study period. Sixty seven (64.4%) were primigravida and most (n=59, 56.7%) parturients were of age group 20-30 years. The commonest (n=65, 62.5%) indication for vacuum application was prolonged second stage of labor. Among the maternal morbidities, 6.7% (n=7) had genital tract injury, 3.8% (n=4) had primary post-partum hemorrhage, 3.8% (n=4) had urinary retention, 2.8% (n=3) needed blood transfusion. Among neonatal morbidity indicators, 19.2% (n=20) neonates had birth asphyxia, 4.8% (n=5) neonates had cephalohematoma, 0.96% (n=1) had brachial plexus injury. There was one early neonatal death due to meconium aspiration syndrome.Conclusion: A successful vacuum assisted delivery can be achieved with lesser maternal and neonatal morbidity with timely assessment of labor, skilled operator, and availability of neonatal team.J. Lumbini. Med. Coll. Vol 4, No 2, July-Dec 2016, Page: 104-107DOI: https://doi.org/10.22502/jlmc.v4i2.101